Adaptasi Alat Ukur Nicomachus-Positive Parenting Indonesia: Pengasuhan Psikologi Positif - Marissa Chitra Sulastra; Ni Luh Ayu Vivekananda (IDEA: Jurnal Psikologi, 2025)
Parenting is a significant topic in developmental psychology, widely discussed among both scholars and the general public. Positive psychology-based parenting is a promising area of study, as it can support both parents and children in achieving well-being in their lives. This study aims to adapt the Nicomachus-Positive Parenting (NPP) scale into the Indonesian language. The NPP is a measurement tool developed by Thodoros A. Kyariazos and Anastassios Stalikas in 2019. It is grounded in the principles of positive psychology and consists of four factors: nurturing values, strength identification & boosting, parenting context, and involvement. This study involved 203 parents with children aged 7–13 years. The results of the Confirmatory Factor Analysis (CFA) indicate that the 16-item scale demonstrated a good model fit (X²/df = 1.588; RMSEA = 0.054; RMR = 0.040; GFI = 0.916; CFI = 0.931; TLI = 0.911; AGFI = 0.876; IFI = 0.933). Cronbach's Alpha calculation further confirmed the reliability of the instrument (α = .817, p ≤ .001). Therefore, the findings suggest that the Indonesian version of the Positive Psychology Parenting scale is a valid and reliable measurement tool.